การวิเคราะห์ประสิทธิภาพในการซื้อขายหลักทรัพย์โดยใช้เรย์โนลด์นัมเบอร์ กรณีศึกษาดัชนีหลักทรัพย์แนสแด็ก - ธาดารัตน์ พรมเทศ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study aims to examine proxy of securities trading base on Reynolds number theory and analysis of the efficiency of stock trading using Reynolds number. Which the value represents the change of fluid from laminar flow to turbulent flow, considering all 3 components are price, trading volume and time. All element like an economic vector has movement in economics system. In the pipe has hypothetical line with independent movement. When the securities like a fluid particle that are moving circular motion or rotary-spiral trajectories around hypothetical line causing the lines to look broken. showing the fluctuation of securities that affect the price of securities. The study will analyze the NASDAQ Index data from 2007 to 2018, a total of 3,030 data and the data will be divided into 3 parts as follows (1) 2007-2010 (2) 2011-2014 and (3) 2015 -2018, in which each period will study according to the type of investment in all 3 cases which are short-term investment, medium-term investment, long-term investment. Compare securities analysis between Reynolds number and technical that investors. Often used in securities analysis such as Relative Strength Index (RSI), Exponential Moving Average (EMA) and Moving Average Convergence Difference (MACD). The results of the study that securities analysis using technical methods. The tools that can provide the most return on investment securities is Reynolds number method. Due to considering all 3 variables at the same time, including prices, trading volume and time and from the above studies, show that investors can use the Reynolds number method as a tool for securities analysis to help them invest in the future.